PENGELOLAAN KOLEKSI PERPUSTAKAAN SEKOLAH MENENGAH ATAS NEGERI 8 KABUPATEN BATANGHARI PROVINSI JAMBI - Uzla, Nurmaili; Putri, Riska Amalia (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
Management of Library collections at State High School 8, Batanghari Regency, Jambi Province. The Library is one of the infrastructure facilities that every school must have. The aim of this research is to optimization of library collection management at SMAN Negeri 8 Batanghari regency, Jambi province. The method used in this research is descriptive qualitative. The results of the research show that (1) The flow of library collection management at SMA Negeri 8 Batanghari Regency, jambi Province is inventory, classification, cataloging, making library equipment, arranging library collections on library shelves. The majority og library collection management is carried out by the library manager of state High School 8, Batanghari Regency, Jambi Province. (2) Barriers to managing library collections at SMA Negeri 8 Batanghari Regency, Jambi Province (3) Effort to prevent several obstacles in the process of managing library collections at SMA Negeri 8 Regency, Jambi Province. Keywords: Library Management, Management, Library Collection.